2021
DOI: 10.1101/2021.05.13.444068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influenza A virus defective viral genomes are inefficiently packaged into virions relative to wild-type genomic RNAs

Abstract: Deletion-containing viral genomes (DelVGs) are commonly produced during influenza A virus infection and have been implicated in influencing clinical infection outcomes. Despite their ubiquity, the specific molecular mechanisms that govern DelVG formation and their packaging into defective interfering particles (DIPs) remain poorly understood. Here, we utilized next-generation sequencing to analyze DelVGs that form de novo early during infection, prior to packaging. Analysis of these early DelVGs revealed that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…similar finding; that HA readily accumulates deletions within cells, but that these deletions are generally lost during packaging (Alnaji et al, 2021). Our study, which provides length variation above that found in natural populations, provides an explanation in the form of divergent requirements in the amount of sequence necessary for efficient packaging.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…similar finding; that HA readily accumulates deletions within cells, but that these deletions are generally lost during packaging (Alnaji et al, 2021). Our study, which provides length variation above that found in natural populations, provides an explanation in the form of divergent requirements in the amount of sequence necessary for efficient packaging.…”
Section: Discussionsupporting
confidence: 78%
“…The divergence in packaging between PB1 and HA also underscores the capacity of this step in the viral lifecycle to shape the distribution of defective viral segments. A recent report described a similar finding; that HA readily accumulates deletions within cells, but that these deletions are generally lost during packaging ( Alnaji et al, 2021 ). Our study, which provides length variation above that found in natural populations, provides an explanation in the form of divergent requirements in the amount of sequence necessary for efficient packaging.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…4B) [22,98]. Such polymerase translocations might be affected or directed by A/U-rich sequences, which have been observed near DVG breakpoints [108,109]. It is possible that such A/U-rich sequences facilitate separation of the template and nascent strand prior to translocation.…”
Section: Aberrant Replication Products and Their Synthesismentioning
confidence: 99%